Vaginal ranking profile vaginal relaxation. - Herrera Calmet, Abelardo (2015)
Vaginal profile is a numerical rating system that correlates the six possible lesions or genital prolapse vaginal relaxation, with all three segments of the vagina. This classification system has been adopted in our department to consider it practical, simple, fast performance and allows a uniform assessment of the evolutionary stage of the process, facilitating what is very important, communication of findings and results.